2018
DOI: 10.1016/j.redox.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurons require a large pool of glutathione to sustain dendrite integrity and cognitive function

Abstract: Loss of brain glutathione has been associated with cognitive decline and neuronal death during aging and neurodegenerative diseases. However, whether decreased glutathione precedes or follows neuronal dysfunction has not been unambiguously elucidated. Previous attempts to address this issue were approached by fully eliminating glutathione, a strategy causing abrupt lethality or premature neuronal death that led to multiple interpretations. To overcome this drawback, here we aimed to moderately decrease glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
1
28
0
1
Order By: Relevance
“…Further analysis showed that the decreases in GSH were not secondary to tissue atrophy. Interestingly, two recent studies in mice that used knockdown of the catalytic subunit of glutamate cysteine ligase, the rate limiting enzyme for GSH biosynthesis in all neurons [ 66 ] or only forebrain neurons [ 67 ], to specifically reduce neuronal GSH levels, showed an enhanced, age-dependent development of cognitive deficits relative to control animals, supporting the idea that GSH loss contributes to cognitive impairments in aging and AD. Importantly, in the former study [ 66 ], the decrease in GSH levels in the hippocampus was modest but comparable to that seen in MCI and AD subjects [ 65 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further analysis showed that the decreases in GSH were not secondary to tissue atrophy. Interestingly, two recent studies in mice that used knockdown of the catalytic subunit of glutamate cysteine ligase, the rate limiting enzyme for GSH biosynthesis in all neurons [ 66 ] or only forebrain neurons [ 67 ], to specifically reduce neuronal GSH levels, showed an enhanced, age-dependent development of cognitive deficits relative to control animals, supporting the idea that GSH loss contributes to cognitive impairments in aging and AD. Importantly, in the former study [ 66 ], the decrease in GSH levels in the hippocampus was modest but comparable to that seen in MCI and AD subjects [ 65 ].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, two recent studies in mice that used knockdown of the catalytic subunit of glutamate cysteine ligase, the rate limiting enzyme for GSH biosynthesis in all neurons [ 66 ] or only forebrain neurons [ 67 ], to specifically reduce neuronal GSH levels, showed an enhanced, age-dependent development of cognitive deficits relative to control animals, supporting the idea that GSH loss contributes to cognitive impairments in aging and AD. Importantly, in the former study [ 66 ], the decrease in GSH levels in the hippocampus was modest but comparable to that seen in MCI and AD subjects [ 65 ]. Thus, age- and AD-dependent decreases in GSH levels may make the elderly particularly susceptible to damage associated with the age- and AD-dependent increases in the concentrations of iron and copper in the brain [ 14 , 25 ] and thereby initiate a feed forward cycle of cell damage and death.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the activity levels corroborate the TAS measures, but only in this region. Recently, it has been demonstrated that HIP requires large pools of glutathione to sustain dendritic integrity [62]. Therefore, it is plausible that glutathione may be the dominate antioxidant in the HIP, thus driving the measure of TAS for that region.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other cellular antioxidants that target a specific type of ROS, GSH is an endogenous compound that protects against multiple oxidative insults (Mizui, Kinouchi et al 1992;Dringen, Pawlowski et al 2005). Notably, neurons require high levels of GSH to counteract oxidative stress and maintain proper brain structural integrity and cognitive function (Fernandez-Fernandez, Bobo-Jimenez et al 2018).…”
Section: The Link Between Psychogenic Stress Brain Energetics and Oxmentioning
confidence: 99%